SPORT STUDENT FOREIGN LANGUAGE LEARNING AND USE HABITS - Rudzinska, Ieva; Jakovļeva, Monta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to analyze sport student foreign language (English) learning and use habits in longitudinal scale (past, present and future prospective). Subjects are 35 Latvian Academy of Sport Education Full and Part time students. Methods: mixed – qualitative and quantitative. Interviews with three students led to designing a questionnaire, consisting of 12 statements. Results were analyzed with SPSS 17.0. Results show that students learn and use English both in sportive and non-sportive environment, active sporting life promotes foreign language learning. Most of them self-assess their English use skills as moderate. At present they use English more than in past, in future more than in present, and in future much more than in past (r=0.5, p<0.001).